Solitary colonic polypoid ganglioneuroma - Funez Rafael; Rodriguez Francisco; Pereda Teresa; Mendez Isabel; Sanchez Andres (BMC, 2008)
Abstract This short report discusses a case of solitary colonic polypoid ganglioneuroma associated with melanosis coli in a woman with no systemic manifestations. To our knowledge this is the first ganglioneuroma reported in the literature in association with melanosis coli. The nature and significance of this event remains unclear, although this may be coincidental due to the laxative intake. Further investigation is necessary to clarify this point. The interest of this case lies moreover in the rarity of this entity and its endoscopic and histologic resemblance to sessile polyps frequent in the clinical practice.